The Impact of Digital Transformation on the Financial Efficiency of Startup Companies - Bella, Shinta; Apriyanti, Nike; Sriwijayanti, Hari (SAFE-Network, 2025)
Financial efficiency is a critical determinant of survival and growth for startup companies operating under resource constraints and market volatility. Digital transformation offers a pathway to optimize financial operations through automation, cloud-based systems, and data-driven decision-making. This literature-based study explores the impact of digital transformation on financial efficiency in startups by synthesizing findings from recent peer-reviewed research. The analysis identifies three core thematic areas: (1) the use of digital tools to enhance financial optimization, (2) improved financial agility through real-time responsiveness and scalability, and (3) persistent constraints and disparities in digital adoption across sectors and geographies. While digital systems enable leaner operations and improved financial oversight, their impact is often limited by inadequate infrastructure, low digital literacy, unclear return on investment, and lack of strategic alignment. To address these challenges, the study recommends phased adoption strategies, public investment in digital infrastructure, targeted training programs, and the development of context-sensitive digital readiness frameworks. These practical insights support a more inclusive and effective use of digital transformation among startups. The review concludes that digital transformation, when approached strategically and equitably, holds significant potential to enhance the financial performance and resilience of early-stage ventures.